Effect of different lysine-metabolized energy ratio on performance of meat-type geese - Dobos, Ádám; Bársony, Péter; Posta, János; Babinszky, László (Acta Agraria Debreceniensis, 2017)
The aim of the experiment was to determine, how the different ratios of the digestibility lysine/ metabolized energy (0.82, 0.87, 0.91 g DLYS/MJ AMEn) of the feed influence the performance of geese. There were 150 goslings (3 treatments, 5 cages/treatments, 10 birds/cages). The experiment has started and finished at the age of 3 and 9 weeks, respectively. The results of the experiment showed, the different ratios of DLYS/AMEn (0.82, 0.87, 0.91 g DLYS/MJ AMEn) did not influence the performance of young geese. Better growth performances were found for the 0.91 g DLYS/AMEn feed (feed intake, body weight gain, feed and energy conversion rate). This treatment coincided with high feeding costs. Based on these results we need more models and farm experiments to prove this tendency.